Rancang Bangun Mesin Pencacah Limbah Nilam - Faradilla Faradilla; Devianti Devianti; Ramayanti Bulan (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Abstrak. Nilam merupakan semak tropis yang menghasilkan minyak atsiri atau sering disebut sebagai minyak nilam. Tanaman ini pada umumnya dimanfaatkan pada bagian daunnya untuk diekstraksi minyaknya serta diolah menjadi parfum, bahan dupa, minyak atsiri, antiserangga, dan digunakan pada industri kosmetik. Tujuan dari penelitian ini adalah untuk merancang bangun mesin pencacah limbah nilam agar mampu limbah nilam menjadi berukuran kecil dan mudah terjadinya terdekomposisi dalam proses pengomposan.Prosedur penelitian ini dilakukan beberapa tahapan yang meliputi proses perancangan mesin pencacah limbah nilam, menentukan mekanisasi kerja dari mesin pencacah limbah nilam, analisa teknik serta melakukan pengujian struktural dan fungsional mesin. Analisa perancangan mesin pencacah limbah nilam yang dihasilkan yaitu kekuatan potong 376.380,27 N, torsi mata pisau 63.984,64 N.m, kecepatan poros mata pencacah 600 rpm, putaran mesin 1600 rpm, kebutuhan daya 5,38 Hp dan diameter poros 25,4 mm. Persentase cacahan limbah nilam untuk pengulangan 1 sebesar 79%, pengulangan 2 sebesar 80,5%, dan pengulangan 3 sebesar 79,8% Pengujian karakteristik limbah nilam menjadi acuan dalam perancangan mesin, karakteristik yang diuji adalah dimensi limbah batang nilam terbesar adalah 279 mm, bulk density sebesar 0,1549 gr/cm3, angle of repose pada plat besi sebesar 39◦, kadar air limbah nilam sebesar 13%, dan koefisien gesek pada plat besi sebesar 32◦."Patchouli Waste Crushing Machine Design" Abstract. Patchouli is a tropical shrub that produces essential oils or often referred to as patchouli oil. This plant is generally used on the leaves for oil extraction and processing into perfumes, incense ingredients, essential oils, insect repellents, and is used in the cosmetic industry. The purpose of this research is to design a machine for chopping patchouli waste so that patchouli waste can be small and easy to decompose in the composting process. Technical analysis as well as conducting structural and functional testing of machines. The analysis of the design of the cutting machine for patchouli waste produced is 376,380.27 N, blade torque 63,984.64 N.m, chopper blade speed of 600 rpm, engine speed of 1600 rpm, power requirement of 5.38 Hp and shaft diameter of 25.4 mm. The percentage of chopped patchouli waste for repetition 1 is 79%, repetition 2 is 80.5%, and repetition 3 is 79.8%. Testing the characteristics of patchouli waste becomes a reference in machine design, the characteristics tested are the dimensions of the largest patchouli waste are 279 mm, bulk density is 0.1549 gr/cm3, angle of repose on iron plate is 39◦, water content of patchouli waste is 13%, and coefficient of friction on iron plate is 32◦. Abstract. Patchouli is a tropical shrub that produces essential oils or often referred to as patchouli oil. This plant is generally used on the leaves for oil extraction and processing into perfumes, incense ingredients, essential oils, insect repellents, and is used in the cosmetic industry. The purpose of this research is to design a machine for chopping patchouli waste so that patchouli waste can be small and easy to decompose in the composting process. Technical analysis as well as conducting structural and functional testing of machines. The analysis of the design of the cutting machine for patchouli waste produced is 376,380.27 N, blade torque 63,984.64 N.m, chopper blade speed of 600 rpm, engine speed of 1600 rpm, power requirement of 5.38 Hp and shaft diameter of 25.4 mm. The percentage of chopped patchouli waste for repetition 1 is 79%, repetition 2 is 80.5%, and repetition 3 is 79.8%. Testing the characteristics of patchouli waste becomes a reference in machine design, the characteristics tested are the dimensions of the largest patchouli waste are 279 mm, bulk density is 0.1549 gr/cm3, angle of repose on iron plate is 39◦, water content of patchouli waste is 13%, and coefficient of friction on iron plate is 32◦.